PROSES BERPIKIR MAHASISWA QUITTER DALAM MENYELESAIKAN MASALAH GEOMETRI DENGAN PEMBERIAN SCAFFOLDING DI JURUSAN PENDIDIKAN MATEMATIKA IAIN BUKITTINGGI - M.Imamuddin, M.Imamuddin (IAIN Batusangkar, 2017)
The role of lecturers to improve students mathematical errors and to lead students to achieve higher potential developments is by (1) facilitating students to connect their current knowledge to the previous ones, (2) encouraging students to continue learning, (3) providing sufficient assistance (scaffolding) to the students toward independence, (4) trigger students to always think so that the development of the scheme is always increasing, and (5) help students internalize the knowledge so that ultimately can construct his knowledge. Scaffolding is one way to assist students in overcoming difficulties solving geometry problems. The purpose of this research is to describe quitter students' thinking process in solving geometry problem by giving scaffolding in Mathematics Education Department of IAIN Bukittinggi. This research employs qualitative research that seeks to express in depth the process of thinking of quitter students in solving geometry problem by giving scaffolding, by using study process of student mathematics concept and its diagnosis through cognitive map. The results showed that quitter students' thinking process in solving geometry problem with scaffolding was unique and interesting. Each student has different ways of solving problems. Problem of difficulty are also experienced by quitter students. Scaffolding provided varies according to the needs of each student to develop his thinking process. By providing scaffolding in general, the process of thinking the subject of research to develop in line with the structure of the problem.